1992
DOI: 10.2307/40285555
|View full text |Cite
|
Sign up to set email alerts
|

On Vibration Sensation and Finger Touch in Stringed Instrument Playing

Abstract: The vibration levels in four traditional stringed instruments during playing have been investigated, including the double bass, violin, guitar, and the piano. The vibration levels, which were measured at several positions and at different dynamic levels, were evaluated with respect to reported thresholds for detection of vibrotactile stimuli. The results show that the vibration levels are well above threshold for almost all positions on the instruments in normal playing. It is concluded that the perceived vibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 10 publications
3
44
2
Order By: Relevance
“…Askenfelt and Jansson showed that vibrations perpendicular to the side of the neck, measured on four violins of varying quality during playing a single note (lowest G, 196 Hz), were above or very close to vibration sensation thresholds measured at the fingertip under passive touch conditions by Verrillo [61]. However, no evidence was found that higher neck vibration intensity would result in judging a violin as being of better quality [4]. One limitation of that study was that for the piano-is that Verrillo's thresholds may not fully reflect actual vibration detection offsets when the left hand holds the neck of the violin (e.g., differences in location and size of contact area, pressure exerted from the hand on the neck).…”
Section: Vibrotactile Feedback At the Left Handmentioning
confidence: 94%
See 2 more Smart Citations
“…Askenfelt and Jansson showed that vibrations perpendicular to the side of the neck, measured on four violins of varying quality during playing a single note (lowest G, 196 Hz), were above or very close to vibration sensation thresholds measured at the fingertip under passive touch conditions by Verrillo [61]. However, no evidence was found that higher neck vibration intensity would result in judging a violin as being of better quality [4]. One limitation of that study was that for the piano-is that Verrillo's thresholds may not fully reflect actual vibration detection offsets when the left hand holds the neck of the violin (e.g., differences in location and size of contact area, pressure exerted from the hand on the neck).…”
Section: Vibrotactile Feedback At the Left Handmentioning
confidence: 94%
“…These psycholinguistic investigations provide empirical evidence that vibrations from the violin body and the bowed string (via the bow) are used by violinists as extra-auditory cues that not only help better control the played sound [4], but also contribute to a crossmodal audio-tactile assessment of its attributes. The perception of …”
Section: Touch and The Conceptualization Of Violin Quality By Musiciansmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have usually tried to associate peculiarities in this behavior to specific sound qualities of the instrument itself. The only work we know about, which specifically addressed the issue of describing the vibrational behavior of an instrument from a player's haptic perception perspective is one by Askenfelt and Jansson [2]. The authors examined the vibrating behavior of several stringed instruments (violin, guitar, double bass, piano) by means of accelerometers, placed on different positions, and holography measurements to identify the patterns of several low-frequency vibration modes.…”
Section: Motivationsmentioning
confidence: 99%
“…Haptically rendered instruments are designed to remove a major flaw in otherwise useful practise instruments; namely, the absence of an authentic sense of touch, or feel, which accompanies almost any instrumental interaction [16]. Feel can be simply defined as force felt by a player at the point of contact with an instrument; a brass player feels the vibration of his lips [19], a violinist experiences vibration and resistance at the point where the bow is held and where the string is depressed [1], a pianist feels different levels of resistance at the key [7] [8] and so on.…”
Section: Haptics and Musical Instrumentsmentioning
confidence: 99%